Mr. Rosaen's magical thinking: A short evaluation of Alex Rosaen's 2013 prevailing wage methodology - Peter Philips (The University of Utah, Department of Economics, 2013)
This paper critically reviews Alex L. Rosaen, The Impact of Michigan's Prevailing Wage Law on Education Construction Expenditures, Anderson Economic Group, LLC, Commissioned by the Associated Builders and Contractors of Michigan, 2013. It is shown that Rosaen's estimates of the prevailing wage regulatory impact on Michigan educational capital outlays swing widely from negative to positive based on the assumptions used in his model. Further it is shown that the bases for Rosaen's assumptions are outdated and miscalculated. An alternative methodology using statistical tests is suggested that provides more stable results. Two alternative examples are presented. This critique concludes that Rosaen's estimates are unreliable.
Keywords: J24; J28; J8; J68; 330; prevailing wage; capital outlays; education; construction; Michigan